Hydrogeological Conceptual Analysis with FEFLOW, for the Ccoyahuacho Slope - Andahuaylas - Peru - Gutierrez, Ruben Esau Mogrovejo (2023)
The purpose of this research project is to develop a hydrogeological model using FEFLOW software, aiming to obtain seepage rates in the 03 soil layers due to rainfall recharge in the Ccoyahuacho slope, and subsequently install drains. Through soil mechanics studies, results of poorly graded gravel, well-graded gravels were obtained, and with the geological study, Andesite rock was identified. Furthermore, the hydrological study yielded an intensity of 227.33 mm/h for a 15-minute duration and a 100-year return period. Additionally, a topographic survey was conducted using the Phantom 4 RTK drone, obtaining 149,354 UTM 18S topographic points. The application of the hydrogeological model resulted in a seepage rate of 0.0002 l/s without drain installation. With the subdrain installed, a seepage rate of 878.1 l/s was achieved, indicating that the flow is directed towards the drainage system. Thus, the drain is functioning based on the input parameters in the software.